Voices of rural farmers in Suriname about climate change, agricultural innovation and landscape managementTT - Les voix des agriculteurs ruraux du Suriname sur le changement climatique, l’innovation agricole et la gestion du paysage - Helstone, Anwar (Institut national de la recherche agronomique (France). Centre de recherches, 2016)
Many rural areas in Suriname lack information on the technology provided by officials of the government extension agency and research institutes. As part of a baseline study for the sixth operational strategic plan of the Small Grants Programme in Suriname, four communities were selected. The purpose of this study was to collect data from these communities on issues related to climate change, agricultural innovation and landscape management. According to the results, the communities have a good knowledge of the management of their landscapes. Improved farm management will be possible through access to innovative and new knowledge developed in and out of the community. Climate change is an important issue that the community is already aware of, they have developed their own local strategy of resilience to this issue.